A Popular Culture Phenomenon Of Fear Missing to Karen's Diner Restaurant Brainstorming Based on Harjani Hefni’s Perspective in Islamic Communication - Nabila Nikmatul Laeli; Zhila Jannati (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2023)
The aim of this research was to find out western popular culture that could cause Fear of Missing Out to social media users regarding the brainstorming carried out by Karen's Diner Restaurant in branding food and drinks. This research used Hefni Harjani's Islamic communication theory with a qualitative descriptive research and uses data collection techniques as participant observers, through Instagram media on the Reels Instagram section. The results found in this research were the brainstorming process carried out by Karen's Diner Restaurant which deliberately used the concept of cultural differences, which were contradictory or binary opposition which viewed that differences were fundamental to all languages and thoughts so that the term “fear of missing out” or known as fomo. These cultural differences, of course, make a bad culture that was not in accordance with the concept of communication science which was applied through the Al-Quran from the perspective of Hefni Harjani. Also in this research, it was found that the brainstorming conducted by Karen's Diner was very influential in changing the behavior of people who visited, thereby creating a new trend with the term fomo towards the community because of the help from influencers.